2017
DOI: 10.1111/cen.13456
|View full text |Cite
|
Sign up to set email alerts
|

Bone markers in polycystic ovary syndrome: A multicentre study

Abstract: Bone formation markers were decreased in younger women with PCOS when compared with healthy women, which may affect bone mass in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…The important prohormone 25OHD influences BMD by regulating calcium metabolism, but 25OHD per se may not have any significant influence on BTMs (37). Even though 25OHD levels showed an increasing trend in non-obese and obese subjects in both treatment groups, significant increases were observed only in the non-obese subjects treated with metformin and obese subjects treated with placebo.…”
Section: Tablementioning
confidence: 88%
“…The important prohormone 25OHD influences BMD by regulating calcium metabolism, but 25OHD per se may not have any significant influence on BTMs (37). Even though 25OHD levels showed an increasing trend in non-obese and obese subjects in both treatment groups, significant increases were observed only in the non-obese subjects treated with metformin and obese subjects treated with placebo.…”
Section: Tablementioning
confidence: 88%
“…Hyperandrogenism and hyperinsulinemia, well-recognized characteristics of PCOS, may influence bone mineral density and biochemical markers of bone turnover. Bone formation markers were found to be decreased in younger PCOS patients compared with healthy controls [66]. It has also been reported that metformin and sulfonylureas may have a neutral or positive effect on bone health [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different OC levels in subjects with PCOS are supposed to be responsible for the heterogeneity of this syndrome [163]. Contrastingly, a multicentric study, that evaluated 298 women with PCOS and 194 healthy controls, reported that OC levels were decreased in PCOS patients compared with controls [164]. Taking into account the precursor of osteocalcin, the undercarboxylated form, a study reported its regulatory role in energy metabolism by promoting insulin release and increase of adiponectin production [165].…”
Section: Other Implications Due To Oxidative Stressmentioning
confidence: 99%